Factors Related to Personal Hygiene of Traditional Jamu Handler in Bantul District, Indonesia - Dyah Suryani; Atika Rahma Indriani; Suyitno Suyitno (GHMJ (Global Health Management Journal))
Background: Foodborne disease is the contamination of pathogenic bacteria that multiply in drinks. Traditional jamu handlers, people who process conventional jamu, need to implement and understand the importance of personal hygiene to avoid bacterial contamination.